Chinese government in Ming times : (Columbia University Press, 1969)
Preface Charles O. Hucker vii; Ming Local Administration Lien-Sheng Yang 1; Yuan Origins of the Wei-so System Romeyn Taylor 23; Policy Formulation and Decision-Making on Issues Respecing Peace and War Jung-Pang 41; Fiscal Administration During the Ming Dynasty Ray Huang 73; Ming Education Intendants Tilemann Grimm 129; Academies and Politics in the Ming Dynasty John Meskill 149; The Ming Dynasty Bureaucracy: Aspects of Background Forces James B. Parsons 175; Notes 233; Glossary 273; Index 277.